PENERAPAN METODE GLOBAL BERBANTUAN MEDIA RODA PINTAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA SD IT ANNURILLAH KECAMATAN BERINGIN - Anjani, Yulia; M. Faisal Husna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to improve students' reading skills through the application of the global method assisted by the "smart wheel" media. This research uses a Classroom Action Research (CAR) approach, conducted in two cycles, and employs a quantitative method. The data collection instruments used in this study include student observation sheets, teacher activity observation sheets, and documentation. The subjects of this study were 29 second-grade students at SD IT Annurillah Beringin.The results of the study showed a significant improvement in students' reading skills, as evidenced by the average percentage scores on the student observation sheets. In Cycle I, the average score for students' reading ability was 66.86%, while in Cycle II, the average score increased to 84.09%, reflecting an improvement of 17.23%. Meanwhile, the average score on the teacher activity observation sheets in Cycle I was 71.87%, and in Cycle II, it increased to 89.06%, indicating an improvement of 17.19%. Based on the findings above, it can be concluded that the implementation of the global method assisted by the "smart wheel" media effectively improves the reading skills of students at SD IT Annurillah Beringin.